2021
DOI: 10.4103/eus-d-20-00207
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning with convex probe endobronchial ultrasound multimodal imaging: A validated tool for automated intrathoracic lymph nodes diagnosis

Abstract: Background and Objectives: Along with the rapid improvement of imaging technology, convex probe endobronchial ultrasound (CP-EBUS) sonographic features play an increasingly important role in the diagnosis of intrathoracic lymph nodes (LNs). Conventional qualitative and quantitative methods for EBUS multimodal imaging are time-consuming and rely heavily on the experience of endoscopists. With the development of deep-learning (DL) models, there is great promise in the diagnostic field of medical ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Traditional time-based progression apprenticeship models for ultrasound training face numerous challenges. [ 80 81 82 83 ] This “see one, do one, teach one” approach falls victim to the aforementioned barriers. Despite these challenges, some medical institutions have committed to comprehensive integration of ultrasound instruction across all years of medical school.…”
Section: The Role Of Ultrasound Simulationmentioning
confidence: 99%
“…Traditional time-based progression apprenticeship models for ultrasound training face numerous challenges. [ 80 81 82 83 ] This “see one, do one, teach one” approach falls victim to the aforementioned barriers. Despite these challenges, some medical institutions have committed to comprehensive integration of ultrasound instruction across all years of medical school.…”
Section: The Role Of Ultrasound Simulationmentioning
confidence: 99%
“…EBUS imaging can reflect the characteristics of LNs, and it has been demonstrated in several studies that certain EBUS features can be used to distinguish between benign and malignant intrathoracic LNs during EBUS-TBNA. [ 8 10 ] However, ultrasonic characteristics of LNs are different between various malignant diseases, which may affect the judgment to predict metastatic LNs. [ 11 ] Previous studies have individually demonstrated that grayscale feature, Doppler mode, and elastography may assist clinicians to predict LN metastasis during EBUS-TBNA.…”
Section: Introductionmentioning
confidence: 99%